Early brain radiotherapy combined with third-generation EGFR-TKIs improves survival in EGFR-mutant NSCLC with synchronous brain metastases: a multi-center retrospective analysis - Kong, Yaru; Sun, Yunchuan; Xiao, Li; Lu, Hongling; Wang, Rui; Yu, Yongchao; Zhou, Jianxi; Zhang, Jiaju; Zhou, Yingnan (Frontiers in Oncology, 2026)
ObjectiveThe optimal timing for combining brain radiotherapy with first-line third-generation EGFR tyrosine kinase inhibitors (TKIs) in patients with EGFR-mutant non-small cell lung cancer (NSCLC) and synchronous brain metastases (BM) remains uncertain. We compared an early combined therapy (ECT) strategy with a salvage radiotherapy (SRT) strategy.MethodologyIn this multi-center retrospective study, patients with newly diagnosed EGFR-mutant NSCLC and synchronous BM receiving first-line third-generation EGFR-TKIs were classified into ECT (radiotherapy within 90 days of TKI initiation without progression, n=83), SRT (radiotherapy at intracranial progression, n=83), and TKI monotherapy (n=27) groups. The primary endpoint was intracranial progression-free survival (iPFS). Secondary endpoints included overall survival (OS) and safety.ResultsThe ECT strategy significantly prolonged iPFS compared to SRT (median 22.4 vs. 15.7 months; hazard ratio [HR] 0.628, 95% CI 0.459–0.858; P = 0.002). OS was also significantly longer with ECT (median 37.5 vs. 31.8 months; HR 0.637, 95% CI 0.465–0.871; P = 0.003). The survival benefit was most pronounced in patients with 1–3 BMs and exon 19 deletions. Multivariate analysis confirmed ECT as an independent favorable prognostic factor. The incidence of grade ≥3 adverse events and specific neurotoxicities was low and comparable between groups.ConclusionFor patients with EGFR-mutant NSCLC and synchronous BM, early brain radiotherapy combined with first-line third-generation EGFR-TKIs is associated with significantly improved intracranial control and overall survival compared to deferring radiotherapy until progression, without a significant increase in severe toxicity. These findings support consideration of an early integrated treatment approach.